Understanding efficiency for better management of enterprises - Adhikary, Dileep K. (1999)
The force of competition has put the enterprises at the mercy of managerial effectiveness. The effectiveness is something beyond the absolute level of profit and returns on investment. Efficiency constitutes the right element in assessing the health of an enterprise. This paper discusses the conceptual basis of examining efficiency and analyses the efficiency level of the manufacturing sector based on 1991/92 and 1996/97 censuses. The paper expects to strike an awakening among the managers and policy makers for regular application of efficiency assessment. - Reproduced
Keywords: Managers; Enterprises; Management